STRATEGIC MANAGEMENT AND OPERATIONAL MANAGEMENT AND THEIR IMPLEMENTATION IN EDUCATIONAL INSTITUTIONS - Rasfiuddin Sabaruddin; Iyan Antono Sibille; Hafid Bahar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The future of humans is greatly influenced by various factors, one of which is education. A good education can be achieved by implementing strategic and operational management in educational institutions. This research will be carried out to see how the implementation of strategic management and operational management in educational institutions will be implemented. This research will be carried out using a qualitative approach. The data in this study come from different research results and previous studies, which are still relevant to this research. The results of this study found that there was a positive impact on the development of educational institutions due to the implementation of strategic and operational management. This advantage is a guide to overcoming various problems and providing opportunities now and in the future. In addition, the accuracy of decision-making and technical implementation will be better.